2021
DOI: 10.4018/978-1-7998-7375-4.ch016
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Book Clubs to Elevate Discussion and Diverse Voices

Abstract: Preservice teachers in educator preparation programs (EPPs) are rarely cognizant of programmatic structures outside their own EPP. This lack of awareness isolates preservice teachers within their own programs and university cultures. As teacher educators, the authors wondered: How might interacting with peers in other EPPs bolster our preservice teachers' disciplinary literacies, praxis, and cultural competency? How might cross-institutional virtual interaction expand preservice teachers' pre-professional netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…Based on research question one, this study demonstrated that the participants had positive perceptions of the online literature circles as majority perceived it as interesting, engaging and they loved it. This finding concurs with studies by Ferdiansyah et al (2020), Fortune et al (2021), andNovitasari et al (2021). The online literature circles successfully provided encouraging and enjoyable learning experiences for learners which develop motivation and positive attitudes towards literature (Dogan et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on research question one, this study demonstrated that the participants had positive perceptions of the online literature circles as majority perceived it as interesting, engaging and they loved it. This finding concurs with studies by Ferdiansyah et al (2020), Fortune et al (2021), andNovitasari et al (2021). The online literature circles successfully provided encouraging and enjoyable learning experiences for learners which develop motivation and positive attitudes towards literature (Dogan et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Although much research has documented the benefits of implementing literature circles, the adoption of online literature circles among pre-service teachers has yet to receive much attention (Ferdiansyah, Ridho, Sembilan, & Zahro, 2020) and needs further investigation. Research into it Arab World English Journal www.awej.org ISSN: 2229-9327 42 would build confidence and increase chances for the use of literature circles in future classroom practice (Fortune, Horst, Kessler, Tackett & Pennington, 2021). This study supports specifically the development in research investigating the use of online literature circles for the training of TESL pre-service teachers in exploring Hamlet, a Shakespeare's play.…”
Section: Literature Reviewsupporting
confidence: 66%